The influence of zeolite and zinc fertilizer application on soil nutrient availability, growth performance and yield of aerobic rice / Nur Farahin Syahirah Mohammad Musa - Mohammad Musa, Nur Farahin Syahirah (Faculty of Plantation and Agrotechnology, 2018)
Rice (Oryza sativa L.) is the second most important cereal crop and cultivated in more than a hundred countries. However, many researchers found zinc (Zn) deficiency symptoms in human health especially in a country where rice is a consumed as a staple food. Zinc deficiency in rice reduces grain yield and the nutritional quality of the grain. Zeolite is a natural super porous mineral that when added to fertilizers can help to retain nutrients and, therefore, improving the long term soil quality by enhancing its absorption ability. The objectives of this study are to assess the benefits of zeolite application and Zn fertilizer on the growth performance and yield of aerobic rice and also to identify the effects of zeolite application on the availability of Phosphorus (P), Potassium (K) and Zn in soil. The experiment was laid out in Completely Randomized Design (CRD) in a greenhouse at UiTM Jasin for 10 weeks. Zinc was applied as ZnCl2 at 0, 15, 25 and 50 ppm with 150 g of zeolite per 100 kg soil and each treatment replicate thrice. The data retrieved from conducted experiment was analyzed using Minitab software on One- Way ANOVA. Results showed that, increasing levels of Zn in soil significantly influenced plant height, length of leaf, and SPAD chlorophyll reading while number of tiller, 100-Grain dry weight and straw yield dry weight did not significantly influenced because the interaction of Zn between other soil components such as Iron (Fe) and Aluminum (Al) Oxide also organic matter, thus the ability of the soil solution to retain plant nutrients is reduced. Zinc availability in soil after harvest showed significant difference with application of zeolite while others nutrients such as P and K showed no significant difference.